An??lise da composi????o corporal por meio de DEXA em crian??as e adolescentes com S??ndrome de Down - Nascimento, Edilson Francisco (2016)
The aim of this study was to evaluate the nutritional status and make a correlation between the use of different assessment protocols most commonly used, compared with DEXA (Dual-energy X-ray absorptiometry) in children and teenagers with Down syndrome (DS) . The sample comprised 41 children and adolescents from both gender, aged between 9 and 19 years old, being 26 with DS from ???Espa??o ConViv??ncias??? Project and 15 volunteers without DS rated as control group (CG). Anthropometric measurements of height, weight, waist circumference and hip, BMI (Body Mass Index) and skinfold thickness were made, and to calculate the the body fat %G it was used four protocols and DEXA. Blood samples were taken for biochemical analysis also applying if you recall 24 hours food intake and the isometric strength test. It was observed that 40% of the control group showed overweight and obesity while in the DS group was detected the rate of overweight and obesity was 50%. The caloric intake in both groups was according to the daily recommendations, but protein intake was above recommended on both groups. The stature, strength and reason force had a significant difference P <0.05 corroborating previous studies where people with Down syndrome have a lower height and strength when compared to the general population. In biochemical analyzes significant changes were shown (P <0.05) to triiodothyronine (T3) between the GC and SD. It was observed that in the DS group in Jackson and Pollock protocol ICC (0.83), r (0.82) and R?? (0.86) and Slaugter ICC protocol (0.74), r (0.79) R2 (0.62) wherein the linear regression analysis indicated that most explanatory power with equation was followed by Jackson and Pollock et al Slaugter. The group with DS showed lower isometric strength when compared to the CG and predisposition to being overweight and even obesity, a problem that can be worsened by poor eating habits. It was concluded that the equations of Slaughter et al would be the most appropriate to determine the %G in children and teenagers with DS by requiring less knowledge from appraiser to perform it, because of the amount folds to be analyzed, requiring less time for implementation and readiness access to the folds. It was noticed, finally, that because this is the first Brazilian study on this subject, there is a need for further studies related to the prediction of body composition in children and teenagers with DS that could promote the development of a specific equation for this audience.